2019
DOI: 10.1111/codi.14618
|View full text |Cite
|
Sign up to set email alerts
|

Sphincter‐sparing surgery for complex anal fistulas: radiofrequency thermocoagulation of the tract is of no help

Abstract: Aim To compare the rate of failure of radiofrequency thermocoagulation for anal fistula with that of rectal advancement flap in a case‐matched study. Method Patients who underwent radiofrequency treatment were compared with age‐ and sex‐matched patients with Crohn's disease (CD) who underwent a rectal flap procedure. Fistula features, general characteristics and the main clinical events were recorded in a prospective database. Failure was defined by at least one of following: abscess, purulent discharge, visib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 15 publications
0
4
1
1
Order By: Relevance
“…These results are superior to a previous case-control retrospective study comparing radiofrequency treatment and advancement flap [32] which showed healing in 25.8% of the cases, with a median follow-up of 5 months. Postoperative complications were higher (three abscesses, a haematoma and a thermal ulceration with a rectovaginal fistula).…”
Section: Discussioncontrasting
confidence: 81%
“…These results are superior to a previous case-control retrospective study comparing radiofrequency treatment and advancement flap [32] which showed healing in 25.8% of the cases, with a median follow-up of 5 months. Postoperative complications were higher (three abscesses, a haematoma and a thermal ulceration with a rectovaginal fistula).…”
Section: Discussioncontrasting
confidence: 81%
“…Although using RF-induced thermofusion to create intestinal anastomosis represents a potentially important advance, it also poses new challenges with welded anastomoses by thermofusion including insufficient coagulation of proteins, necrosis and desquamation of parts of the circumference of the anastomotic zone, leading to dreaded complication of anastomotic leakage and causing failure of the operation. Therefore, technological research is needed to ensure reliable tissue connection and residual viability of the anastomotic zone until the tissue reconstruction is complete [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…This month's Editor's Choice by Merlini l'Héritier et al . evaluated ablation of the tract by applying radiofrequency thermocoagulation . They used a control group, selected from a prospective database consisting of patients who underwent occlusion of the fistula tract by a rectal advancement flap, paired‐matched for sex, age and the presence of Crohn's disease.…”
mentioning
confidence: 99%
“…Crohn's disease is thought to be caused by a failure of the intestinal mucosal immune system to tolerate commensal bacteria. The highest healing rates in the featured study were achieved in patients with Crohn's disease (overall success 64 percent) . All these patients were on anti‐tumour necrosis factor alpha therapy.…”
mentioning
confidence: 99%
See 1 more Smart Citation